1980
DOI: 10.1148/radiology.134.2.7352241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and experimental investigation of a smoothed CT reconstruction algorithm.

Abstract: The usefulness of a smoothed reconstruction CT algorithm was studied using raw data from the EMI Mark I head scanner. The reconstruction algorithm operated on an off-line computer, independent of the EMI algorithm. This technique greatly reduces image noise and improves the visibility of very low-contrast structures, but at the cost of reduced spatial resolution. Phantom tests with contrasts as low as 0.14% demonstrated the validity of the images. Clinical results showed greatly improved visualization of gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Thinner slices reduce partial volume effects and can improve lesion detection, yet unless a compensatory increase in exposure is made, the resultant images have higher noise levels, which may offset any advantage in lesion conspicuity provided by the reduction in slice thickness. Traditional low pass or smoothing algorithms can be used in combination with thinner slices to offset noise increases; however, these algorithms also reduce spatial resolution [14]. Alternatively, recently developed hybrid reconstruction algorithms using iterative techniques have the potential to facilitate thin slices without noise increase [15]; however, studies investigating the interaction between algorithm, slice thickness and exposure when optimising hepatic CT protocols are required.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Thinner slices reduce partial volume effects and can improve lesion detection, yet unless a compensatory increase in exposure is made, the resultant images have higher noise levels, which may offset any advantage in lesion conspicuity provided by the reduction in slice thickness. Traditional low pass or smoothing algorithms can be used in combination with thinner slices to offset noise increases; however, these algorithms also reduce spatial resolution [14]. Alternatively, recently developed hybrid reconstruction algorithms using iterative techniques have the potential to facilitate thin slices without noise increase [15]; however, studies investigating the interaction between algorithm, slice thickness and exposure when optimising hepatic CT protocols are required.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…A poor (but practical) man's version of a prewhitening filter, with respect to the CT negative noise correlations, can be achieved by means of gross image smoothing. Joseph and collaborators (Joseph 1977(Joseph , 1978Joseph et al 1980) have found that in CT this requires first expanding the data scale to maintain numerical precision and then using a low pass filter function with a very low frequency cut off.…”
Section: Performance Of Real Observersmentioning
confidence: 99%
“…A poor (but practical) man's version of a pre-whitening filter--with respect to the CT negative noise correlations--can be achieved by means of gross image smoothing. Joseph has found that in CT this requires first expanding the data scale to maintain numerical precision and then using a filter function with a very poor high frequency response (14).…”
Section: Performance Of Real Observersmentioning
confidence: 99%